Influência da obesidade e periodontite materna sobre a perda óssea alveolar da prole feminina de ratos - Garcia, Gabriela Roza (2021)
Fetal or metabolic programming proposes that the intrauterine environment or the period of childhood can modulate physiological control and homeostasis, increasing the susceptibility to chronic diseases throughout life. The epigenetic mechanisms linked to this association are involved in development programming, in the context of the Developmental Origins of Health and Disease (DOHaD). Among these diseases we have obesity, which is a worldwide public health problem and a risk factor for several diseases, including periodontal disease. The objective of this study is to evaluate the periodontal tissues of the female offspring of obese mothers submitted to experimental periodontitis. For that, twenty female pups of Wistar rats were selected, half of the pups received during the first five days of life subcutaneous injections in the cervical region of 4g / Kg / day of monosodium glutamate (MSG group, n = 10) and the other half received hyperosmotic saline injections, 1.25g / kg / day (CTL group, n = 10). At 70 days of life, both groups were subdivided into two (n = 5) according to the induction of experimental periodontal disease by ligation: control with ligation (CTL-CL), control without ligation (CTL-SL), MSG with ligation (MSG-CL) and MSG without ligation (MSG-SL). Seven days after induction of periodontal disease, CTLs and MSGs were crossed with male control rats (1 male to 2 females). After weaning offspring, the mothers were weighed and euthanized. The offspring (1st generation - F1) were then named according to the treatment given to the mothers: CTL-CL-F1, CTL-SL-F1-, MSG-CL-F1 and MSG-SL-F1 (all n = 12). At 70 days of age, 6 animals from each group of female offspring were submitted to ligation. At the end of the experimental period (100 days), all animals were weighed and euthanized. The jaws were removed, fixed in 10% formaldehyde for 24 hours, decalcified and processed for histological and radiological techniques. The offspring of control mothers with periodontitis (CTL-CL-F1-CL, CTL-CL-F1-SL) showed a significant increase in body weight and the Lee index when compared with the CTL-SL-F1-SL group. In the offspring of obese mothers without periodontal disease (MSG-SL-F1-SL), higher body weight and Lee's index were observed when compared to the offspring of control mothers without periodontal disease (CTL-SL-F1-SL). In the histomorphometry of gingival tissues, the MSG-CL-F1-CL group showed an inflammatory process potentiated in the protection periodontium in relation to the CTL-CL-F1-CL group. Radiographically, it was observed that pups in the MSG-CL-F1-CL group had less alveolar bone loss when compared to animals in the MSG-SL-F1-CL groups or with the CTL-CL-F1-CL group. The obese groups MSG-CL-F1-CL, MSG-CL-F1-SL and MSG-SL-F1-CL showed a significant increase in osteocytes and osteoblasts when compared with groups CTL-CL-F1-CL, CTL-CL-F1 -SL and CTL-SL-F1-CL. Still, we found that regardless of the ligature in the offspring, the pups of obese mothers had smaller areas of root resorption. We conclude that maternal obesity and periodontitis increase adiposity and alters the thickness of the gingival epithelium and connective tissue of female offspring. In addition, maternal hypothalamic obesity performs a protective role, decreasing alveolar bone loss, reducing external root resorption and increasing the amount of alveolar bone cells in the offspring.